CORK1, A LRR-Malectin Receptor Kinase, Is Required for Cellooligomer-Induced Responses in Arabidopsis thaliana - Yu-Heng Tseng; Sandra S. Scholz; Judith Fliegmann; Thomas Krüger; Akanksha Gandhi; Alexandra C. U. Furch; Olaf Kniemeyer; Axel A. Brakhage; Ralf Oelmüller (Cells, 2022)
Cell wall integrity (CWI) maintenance is central for plant cells. Mechanical and chemical distortions, pH changes, and breakdown products of cell wall polysaccharides activate plasma membrane-localized receptors and induce appropriate downstream responses. Microbial interactions alter or destroy the structure of the plant cell wall, connecting CWI maintenance to immune responses. Cellulose is the major polysaccharide in the primary and secondary cell wall. Its breakdown generates short-chain cellooligomers that induce Ca2+-dependent CWI responses. We show that these responses require the malectin domain-containing CELLOOLIGOMER-RECEPTOR KINASE 1 (CORK1) in Arabidopsis and are preferentially activated by cellotriose (CT). CORK1 is required for cellooligomer-induced cytoplasmic Ca2+ elevation, reactive oxygen species (ROS) production, mitogen-associated protein kinase (MAPK) activation, cellulose synthase phosphorylation, and the regulation of CWI-related genes, including those involved in biosynthesis of cell wall material, secondary metabolites and tryptophan. Phosphoproteome analyses identified early targets involved in signaling, cellulose synthesis, the endoplasmic reticulum/Golgi secretory pathway, cell wall repair and immune responses. Two conserved phenylalanine residues in the malectin domain are crucial for CORK1 function. We propose that CORK1 is required for CWI and immune responses activated by cellulose breakdown products.